RESPON TANAMAN CABAI MERAH VARIETAS PRABU TERHADAP PENGGUNAAN TRICHODERMA Sp DALAM MENGENDALIKAN PENYAKIT LAYU FUSARIUM - Iin Arsensi (UIR Press, 2014)
The purpose of this study was to evaluate the response of two varieties of red chilli (Capsicum annuum L.) on the use of Trichoderma sp in controlling Fusarium wilt disease. This study was conducted during four months from November 2012 to February 2013 in South Sempaja Village, Sub District of North Samarinda. The randomized block design (RBD) with four replications was used. The first factor is the application of Trichoderma sp (T), consisting of 4 levels: NoTrichoderma sp application (T0), application of 50 g Tricho compost per plant (T1), application of 10 ml liquid Tricho per plant (T2), and application of 50 g Trichocompost per plant + 10 ml liquid Tricho per plant (T3). The second factor is the variety (V), consisting of two levels: local varieties (V1) and prabu variety (V2). As results, the use of Trichodema sp affected high significance on the plant height, number of fruits per plant, fruit weight per plant, and crop production of red chilies. The highest yield and the lowest intensity of attacks was obtained at the aplication of 50 g Trichocompost + 10 ml liquid Tricho per plant. Local and Prabu varieties affected significantly on the plant height, fruit weight per plant, and fruit production, but it did not affect significantly on the plant height at 15 days after planting and the number of fruit per plant. The highest yield production and the lowest intensity of attacks was obtained at Prabu variety. There was no interaction effect between the factors of Trichodema sp application and varieties on all parameters observed.